2022
DOI: 10.1155/2022/8244497
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Attenuates Angiotensin II-Induced Aortic Remodelling by Inhibiting Oxidative Stress-Induced Activation of the Vascular p38 and NF-κB Pathways

Abstract: Interleukin 10 (IL-10) is a probable anti-inflammatory factor that can attenuate hypertrophic remodelling caused by overloaded pressure and improve cardiac function. In this study, IL-10 was decreased in both the plasma of hypertensive patients and the aortic vessels of angiotensin II (Ang II)-induced hypertensive mice. IL-10 was unable to alter blood pressure in the case of Ang II-induced hypertension. The aortic thickness, collagen deposition, and the levels of fibrosis-associated markers, including collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…IL-10 treatment has been shown to improve SOD and CAT activities, as well as the redox ratio in renal ischemia-reperfusion induced by lipid peroxidation [ 56 ]. Recently, Qiu et al [ 57 ] demonstrated that IL-10 reverses AH-induced vascular hypertrophy, possibly through its antioxidant and anti-inflammatory effects. Moreover, Kaur et al [ 10 ] have highlighted the antioxidant properties of IL-10 by mitigating the antioxidant changes caused by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 treatment has been shown to improve SOD and CAT activities, as well as the redox ratio in renal ischemia-reperfusion induced by lipid peroxidation [ 56 ]. Recently, Qiu et al [ 57 ] demonstrated that IL-10 reverses AH-induced vascular hypertrophy, possibly through its antioxidant and anti-inflammatory effects. Moreover, Kaur et al [ 10 ] have highlighted the antioxidant properties of IL-10 by mitigating the antioxidant changes caused by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic RNA extraction was performed using TRIzol reagent method 15 (Thermo Fisher Scientific, MA, USA). cDNA synthesis and polymerase chain reaction were performed using a QuantiNova SYBR® Green RT‐PCR Kit (QIAGEN, Gilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…As such, IL-10 represents a potential therapeutic target for limiting the progression of Ang II-induced aortic remodeling. 15 Thus, acquiring a thorough comprehension of hypertension and its intricate connection with inflammation reveals promising new avenues for therapeutic interventions. Multiple studies have provided substantial evidence that monotherapy involving reninangiotensin system (RAS) inhibitors can modulate immune cell functions and regulate immune response mechanisms, not solely within the hypertensive patient population but across various other disease contexts as well.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations